Rancangan SOP Penyimpanan Material Limbah Produksi Menggunakan Metode First Waste First Out Pada Divisi Infrastruktur Perhubungan PT. Pindad Persero - Natabita Ayum Adiyuna; Nenden Kostini; Nurillah Jamil Achmawati Novel (Jurnal Serambi Engineering, 2025)
PT Pindad (Persero) is a manufacturing company engaged in the production of defence equipment. In the production process, PT Pindad (Persero) generates various types of waste such as slag, scrap, tap and flash. The management of these wastes is carried out through the remanufacturing process in the Support Department of the Transportation Infrastructure Division. However, irregularities in the storage and distribution of waste cause accumulation, waste of space and operational obstacles. This research proposes the creation of a waste storage SOP using the First Waste First Out (FWFO) method as a solution to waste storage and distribution management. FWFO is the author's design, adapted from the FIFO (First In First Out) method, designed to accelerate waste turnover, prevent quality degradation such as corrosion of metals, and improve operational efficiency. The research was conducted using a qualitative method with primary data sources from interviews with the head of the smelting section and the head of the warehouse, and secondary data sources from literature and previous reports. It is expected that the draft SOP for waste storage using the first waste first out method will effectively reduce the accumulation of waste, maximise the use of waste according to specifications, and improve the efficiency of storage and reprocessing at PT Pindad.